Potential of Local Entomopathogenic Nematodes for Control of the Vine Mealybug, Planococcus ficus - Platt, T.; Stokwe, N.F.; Malan, A.P. (South African Journal of Enology and Viticulture, 2018)
Planococcus ficus, the vine mealybug, is the dominant mealybug pest of grapes in South Africa. To provide an alternative for chemical control, entomopathogenic nematodes (EPNs) were investigated as a biological control agent to be used in an integrated pest management system. Four local EPN species were screened for efficacy against female P. ficus, the most potent of which were Heterorhabditis noenieputensis, with 90% mortality, and Steinernema yirgalemense, with 63%. Since S. yirgalemense was previously shown to be highly effective against a range of pests, the effects of temperature and humidity on the infectivity of S. yirgalemense to female P. ficus were also assessed. The application of S. yirgalemense at 25°C yielded the highest mortality, of 72%, followed by 45% mortality at 30°C, and only 9% mortality when applied at 15°C. Steinernema yirgalemense performed best at 100% relative humidity (RH), resulting in 70% mortality. Decreasing RH levels resulted in decreased mortality (61% mortality at 80% RH, 40% mortality at 60% RH). As a soil-based organism, S. yirgalemense is most effective as a biocontrol agent of P. ficus under conditions of moderate temperature and high humidity. Its lethality to P. ficus, and its status as an indigenous species, indicate its promise as a potential biocontrol agent of the vine mealybug.